ANALISIS PENGARUH PENDAPATAN ASLI DAERAH (PAD), INVESTASI, DAN ANGKATAN KERJA TERHADAP PDRB PROVINSI JAWA TENGAH (PERIODE 1984-2013) - Rio Dwi Putranto; Putut Haribowo; Nur Rini (JOBS (Jurnal Of Business Studies), 2015)
GDRP (Gross Domestic Regional Product) is the total value added generated by all bussines units of local region or the entire amount of the value of final goods and services at one period. GDRP can describe the economic growth of a local region. The high level of economic growth showed that the local area were progresife at the economic conditions.This research analyzed the impact of locally generated revenue, investment, and labor force to GDRP (Gross Domestic Regional Product) of Central Java. This research used secondary data which were taken from some government institutions in Central Java. This research used multiple regression analysis. The data were analysed with T-test for partial testing and F-test for simultaneously testing. The result showed that thelocally generated revenue, investment, and labor force simultaneously affected GDRP of Central Java with significant value of 0.00<0.05 and coefficient of determination (Adjusted R2) of 0.702, which means that the locally generated revenue, investment, and labor force contribution amounting to 70.2% and 29.8% was explained by other variables. It was also found that the locally generated revenue had a positive and not significant impact to GDRP of Central Java with coefficient value of 0.744. Iinvestment and labor force variable had positive and significant impact to GDRP of Central Java with the coefficient value of 4.423 and 4.203 respectively.